Environmental and Economic Impacts of V2X Applications in Electric Vehicles: A Long-Term Perspective for China - Yajie Hu; Richao Cong; Toru Matsumoto; Yajuan Li (Energies)
Electric vehicles (EVs) play a critical role in the transition to transportation electrification and are important for achieving carbon neutrality in this sector. China currently leads the world in EV ownership; however, the energy regulation potential of in-use batteries remains largely untapped in the context of an increasingly saturated EV stock. This study systematically evaluates the long-term benefits of vehicle-to-everything (V2X) applications based on EV sales projections and advancements in battery technology. The results indicate that, without compromising daily travel requirements, V2X applications could enable 109.50–422.37 TWh of annual electricity dispatch by 2030, achieving an estimated economic benefit of 198.92–767.25 billion CNY, and reducing carbon dioxide (CO2) emissions by 45.01–173.60 Mt. By 2060, these figures are projected to increase significantly, with annual dispatchable electricity reaching 4217.39–21,689.43 TWh, generating an economic value of 10.82–55.66 trillion CNY, and reducing CO2 emissions by 118.09–607.30 Mt. Furthermore, V2X applications could substantially contribute to achieving the emission reduction targets outlined in China’s Nationally Determined Contributions (NDCs). These findings highlight that V2X applications, as a transformative solution that promotes deep integration between the transportation and power sectors, enhance cross-sectoral emission reduction synergies and support the realization of carbon neutrality goals.